2018
DOI: 10.1002/hec.3774
|View full text |Cite
|
Sign up to set email alerts
|

Hospitals and the generic versus brand‐name prescription decision in the outpatient sector

Abstract: Health care payers try to reduce costs by promoting the use of cheaper generic drugs. We show strong interrelations in drug prescriptions between the inpatient and outpatient sectors by using a large administrative dataset from Austria. Patients with prior hospital visits have a significantly lower probability of receiving a generic drug in the outpatient sector. The size of the effect depends on both the patient and doctor characteristics, which could be related to the differences in hospital treatment and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Although there are descriptive studies that show high intrahospital adherence to HDF medications (since compliance is not mandatory and there may be medication use outside of the formulary), 12,[36][37][38][39][40] there are very few studies which analyze the effect of alterations in an HDF on the two healthcare settings (in-hospital and out-of-hospital). [9][10][11] On the other hand, there are other kind of studies which show involvement of the hospital in changes in prescribing patterns [41][42][43] and furnish evidence of the specific contextual factors that can affect the impact sought with this type of intervention. This current study allows us to identify the effect of a change not previously analyzed (the inclusion of a new, higher-cost me-too drug) in a therapeutic group not previously studied (SNRIs).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are descriptive studies that show high intrahospital adherence to HDF medications (since compliance is not mandatory and there may be medication use outside of the formulary), 12,[36][37][38][39][40] there are very few studies which analyze the effect of alterations in an HDF on the two healthcare settings (in-hospital and out-of-hospital). [9][10][11] On the other hand, there are other kind of studies which show involvement of the hospital in changes in prescribing patterns [41][42][43] and furnish evidence of the specific contextual factors that can affect the impact sought with this type of intervention. This current study allows us to identify the effect of a change not previously analyzed (the inclusion of a new, higher-cost me-too drug) in a therapeutic group not previously studied (SNRIs).…”
Section: Discussionmentioning
confidence: 99%
“…Education: Many studies have shown that misconception is the main reason for the negative attitude of patients about the efficiency and safety of generic medicines. Education and interaction between patients and health care providers (especially physicians and pharmacists) will be effective in changing this misconception ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mandatory Prescription by INN: As, the names of generic medicines, mostly, reflect the function, nature, effect, and use of medicines, it is too important that prescribers recall more generic medicine names. Therefore, mandatory prescribing by INN (with an e-prescribing system or no) can be an influential option ( 45 , 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients/consumers Education: Many studies have shown that misconception is the main reason for the negative attitude of patients about the efficiency and safety of generic medicines. Education and interaction between patients and health care providers (especially physicians and pharmacists) will be effective in changing this misconception (69). Educational and informational campaigns in television, radio (11,31) , internet (23) and social media (11), local newspapers, business journals, consumer magazines, anthropomorphic images (16), Posters and pamphlets (for example in Japan) (25), are practices of encouraging the use of generic medicines in different countries (3,12,19,33,35,38).…”
Section: Generic Substitution (Gs)mentioning
confidence: 99%
“…Mandatory Prescription by INN: As, the names of generic medicines, mostly, reflect the function, nature, effect, and use of medicines, it is too important that prescribers recall more generic medicine names. Therefore, mandatory prescribing by INN (with an e-prescribing system or no) can be an influential option (45,69). Mandatory generic substitution in the inpatient setting: This policy can be used for patients with lower income and would yield significant costsaving for hospitals if it can be extended to other settings (i.e.…”
Section: Prohibitionmentioning
confidence: 99%